Advanced polymer processing technologies for micro‐ and nanostructured surfaces: A review. Issue 4 (5th March 2023) - Kodihalli Shivaprakash, Nischay; Banerjee, Pratip Sankar; Banerjee, Shib Shankar; Barry, Carol; Mead, Joey
Abstract: Functional surfaces with attractive properties, such as superhydrophobicity and omniphobicity often rely on the synergy between intrinsic material properties and dual scale micro‐ and nano‐hierarchical structures for achieving desired wettability. Historically, engineered liquid repellent surfaces have attracted a great deal of interest from academia and industry due to their broad application prospects. Hence, for several years, there have been significant scientific efforts by researchers exploring state of the art manufacturing technologies that are efficient and yet cost effective to produce functional liquid repellent surfaces at an industrial scale. This technical review summarizes the various advanced and state of the art polymer processing technologies employed to fabricate the micro‐ and nanostructured polymer surfaces, with a special focus given to superhydrophobic and omniphobic applications. Here, we discuss the merits and limitations of each fabrication methods available for micro‐ and nanostructuring of polymer‐based surfaces. In addition, an attempt has been made to provide insight into the relationship between geometry of micro/nanostructures (size and shape) and intrinsic wettability on liquid repellency. A special section has been devoted to feature and document all commercialization efforts, including various commercially available products that were developed in the past decade. Finally, outlook and the development trend in the polymer micro‐ and nanostructured surfaces are highlighted to lead future research. Abstract : Fabrication of micro and nanostructured surfaces and applications.